Acidity (pH) and Dissolved Oxygen Levels as Indicators of Water Quality Around the Tuban Coastal Area - Siti Zainab; Novie Handajani; Hendrata Wibisana (Nusantara Science and Technology Proceedings, 2022)
The coast of Tuban is a fairly dynamic area, where the lives of fishermen depend on fishing efforts. Ecosystem changes that occur in the coastal area of Tuban greatly affect the fishing effort, where one of the parameters that can be observed is the distribution of oxygen content from water bodies on the coast. The purpose of this study was to analyze and map the distribution of acidity content (pH) and its correlation with dissolved oxygen in the coastal area of Tuban. This is based on the fact that research on the distribution of dissolved oxygen has been carried out by many experts, as well as the acidity value of seawater, there have also been those who have done it, only here that needs to be emphasized, that there have not been many dissolved oxygen studies involving other parameters such as acidity pH.